HEPATOPROTECTIVE ACTIVITY OF CORDIA OBLIQUA AGAINST PARACETAMOL-INDUCED LIVER TOXICITY ON WISTAR RATS - SIVAKRISHNAN SIVAGNANAM; PRADEEPRAJ DEVARASU (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The ethanolic extract of Cordia obliqua (EECO) Willd. leaves was evaluated for hepatoprotective activity in Wistar rats by inducing hepatic damage with paracetamol. Methods: The leaves of C. obliqua were dried under shade, segregated, pulverized by a mechanical grinder and passed through a 40 mesh sieve. The powdered plant materials were stored in an air-tight container. The above-powdered materials were successively extracted with ethanol by hot continuous percolation method in Soxhlet apparatus for 24 h. The extract was concentrated using a rotary evaporator and subjected to freeze drying in a lyophilizer till dry powder was obtained. Results: Treatment with EECO at 200 and 400 mg/kg showed significant decrease in serum glutamate-pyruvate transaminase, serum glutamic oxaloacetic transaminase, alkaline phosphatase, and total bilirubin levels and a significant elevation in the total protein, albumin, and globulin levels in serum when compared with paracetamol treated rats. In histological study of liver, the hepatocytes show moderate cytoplasm and moderately enlarged pleomorphic and hyperchromatic nuclei. The portal triads show mild periportal inflammation composed of lymphocytes, and central veins are normal. Conclusion: On the basis of results, we can conclude that the EECO leaves showed potential hepatoprotective activity in rats.